ANALISIS MANAJEMEN TALENTA PADA PROGRAM MANAGEMENT TRAINEE DI INDONESIA MOST ADMIRED COMPANIES 2017-2021 - Aditia Erlangga; Lindawati Kartika (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine and analyze the application of talent management in the Management Trainee program to the most admired companies in Indonesia through the determinants of talent management factors, actors, goals and strategies. Seven HR professionals from seven companies in Indonesia participated in the study, which was conducted between July 2022 and November 2022. The methods used in this study were the NVivo analysis and the AHP analysis. Indonesia's human resource competitiveness is still less than that of Singapore, Malaysia, and Thailand. This necessitates the improvement of HR capabilities in Indonesia and motivates any company to response the challenges posed by the ongoing talent war. One strategy used by many companies is Management Trainee program. The findings of this study show that skills are the most significant talent management factor; leader and top management and also human capital are the most important talent management actors; producing potential company executives is the most significant goal; and attracting is the most significant alternative strategy.